PEMBERDAYAAN PETERNAK IKAN LELE MELALUI TEKNOLOGI BIOFLOK DI KECAMATAN PATUMBAK - YUNILAS YUNILAS; ERI YUSNI; GALIH ARI WIRAWAN SIREGAR; RAYHAN AKBAR; M. FADIL FIKRI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
This community service was carried out in Patumbak Kampung Village, Patumbak District, Deli Serdang Regency. Partners' catfish farming has not developed well. Common problems faced by partners include low knowledge of (1) sources of fish feed ingredients, (2) ration formulation techniques, (3) techniques for making fish pellets, (5) techniques for making local microorganisms, and (6) bio floc technology in Fish farming to increase productivity. Problem-solving methods are through Focus Group Discussion (FGD) methods, training, practical activities, and mentoring. The results of community service activities are obtained by increasing farmers' knowledge about: sources of alternative feed ingredients, feed formulation techniques, pellet manufacturing techniques, waste-based local microorganism production